Anaemia Profile and Inflammation Markers in Stunted Children Under Two Years in Indonesia - Luhung Budiailmiawan; Aryati Aryati; Nursin Abd. Kadir; Laily Indrayanti Yusuf; Lia Gardenia Partakusuma; Louisa Markus; Leni Lismayanti (Children)
Background: Stunting is a common issue affecting children who suffer from chronic malnutrition in Indonesia. The Indonesian government has introduced supplementary food programs for stunted children, but the results have been less satisfactory. This may be due to the presence of anaemia and comorbid diseases. Haematology tests and inflammation markers are necessary to identify these conditions. This study aimed to examine the anaemia profiles and inflammation markers in stunted children under two years old. Methods: A cross-sectional descriptive design with cluster samples and consecutive analysis was used. The study was conducted between December 2023 and March 2024 at the West Nusa Tenggara Hospital and Palabuhanratu Sukabumi Hospital laboratories. Samples were obtained from various Public Health Centres in Sukabumi, West Java, North Maluku, and West Nusa Tenggara. Data collection comprised interviews, measurements, and the assessment of haematology, biochemical, and inflammatory markers. Statistical analysis was conducted using SPSS version 20, which includes descriptive analysis, correlation, comparison, and chi-square tests. Results: Two hundred and ten stunted children were identified with various anaemias and comorbidities. These anaemias included suspected thalassemia (38.1%), iron deficiency (18.1%), and anaemia of chronic diseases (13.3%). Based on the inflammatory markers obtained, TB was suspected (21.4%), inflammatory bowel disease (18.1%) was suspected, and allergic proctocolitis was suspected (31.9%). Conclusions: Analysis of the anaemia profiles and inflammatory markers revealed various types of anaemia and suspected comorbidities in stunted children. It is recommended that anaemia profiles and inflammation markers be assessed at the primary healthcare level.